Potential Brix Levels of Mutant Sugarcane Plants at Different Altitudes - Abdul Jalil; Sri Hartatik; Sholeh Avivi (Universitas Muhammadiyah Jember, 2022)
As ingredient raw Sugarcane industry is one _ commodity plantations that have role strategic in economy in Indonesia. Availability varieties superior sugarcane is one _ reason low production sugarcane national . However , the use of varieties superior could support enhancement production sugarcane in Indonesia. enhancement sugar production through varieties with yield tall more take precedence because could increase sugar yield without increase right capacity sugar factory . Mutation result from sugarcane varieties Bululawang (BL) was obtained three genotype potential have yield high . Brix can be made a reference for measure content yield sugarcane because the more tall degrees the brix so the more sweet solution that . Study this use method observation by directly each location . _ Measurement degree brix done with using a refractometer, with take samples on each sugarcane mutants in every location . The results of the research M1 mutant sugarcane has Highest Brix content (19.5%) and capable of adapt with good at height place ± 62 masl . M3 mutant sugarcane has Highest Brix content (19%) and capable of adapt with good at height place ± 141 masl . M2 mutant sugarcane has highest Brix content (23.4%) and capable of adapt with good at height place ± 512 masl .